2001
DOI: 10.1108/13673270110411724
|View full text |Cite
|
Sign up to set email alerts
|

SMARTVision: a knowledge‐management methodology

Abstract: A myriad of researchers have presented methodologies and frameworks for implementing knowledge‐management. However, frameworks do not provide sufficient detail for executing knowledge‐management initiatives, and existing methods do not adequately address all of the requirements for effective knowledge management. The field of knowledge management has been slow in formulating a universally accepted methodology. This paper reviews the status quo of knowledge‐management methodologies and presents a detailed, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 15 publications
0
35
0
2
Order By: Relevance
“…The KM frameworks can be classified as either prescriptive, descriptive or a combination of the two [70]. [58,48,71,72]. In Figure 2 we illustrate the main streams of disagreements, regarding the KM frameworks.…”
Section: Km Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The KM frameworks can be classified as either prescriptive, descriptive or a combination of the two [70]. [58,48,71,72]. In Figure 2 we illustrate the main streams of disagreements, regarding the KM frameworks.…”
Section: Km Frameworkmentioning
confidence: 99%
“…that, in many cases, the same elements can be found on the opposite order, in different frameworks [48]. Moreover, in many cases different KM frameworks include the same elements, but different terms are used for the same (or similar) activities or processes [75][76][77][78].…”
Section: Fig 2: Major Streams Of Disagreements For Km Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Meso and Smith (Meso and Smith 2000) defined an organizational knowledge management system that provides the creation of new knowledge, the assembly of externally created 8 knowledge, the use of existing knowledge, and the finding of knowledge from internal and external sources. Rubenstein et al (Rubenstein-Montano et al 2001) found that developing a KM methodology is a critical step for organisations that are serious about conducting KM activities. However, these researchers agreed that additional understanding in different types of knowledge is needed.…”
Section: General Issuesmentioning
confidence: 99%
“…Different methods and schemes are provided in Wiig et al (1997), Gore and Gore (1999), Alavi and Leidner (2001), Mentzas (2001), Rubenstein-Montano et al (2001b), Jarrar (2002), Holsapple and Joshi (2002), and Shankar and Gupta (2005); KM methodologies reviews and descriptions of KM methodologies such as Rubenstein-Montano et al (2001a), Lytras and Pouloudi (2003), and Yew Wong and Aspinwall (2004) state how a KM initiative can be proposed. However, they do not recommend appropriate detailed issues where and when a KM initiative can be applied, since they suggest applying it to the whole organizational structure.…”
Section: Introductionmentioning
confidence: 99%